Pemikiran Ikhwan al-Shafa Tentang Struktur dan Hakikat Alam Semesta - Asfiya, M. An’im Fikri (Program Studi Aqidah dan Filsafat Islam STISA Ash-Shofa Tasikmalaya, 2025)
This study aims to reorganize the Ikhwan al-Shafa's Thoughts on the structure and nature of the universe. In the 10th century AD, their view of nature stood out because it integrated nature as a spiritual-metaphysical entity as well as a material one. The author argues that this approach is more relevant to today's needs, especially after modern science, through modern cosmology, for the past few centuries has only recognized nature as a material-physical entity and ignored its spiritual metaphysical aspects. This neglect has reduced the meaning of the universe from its complete nature, which ultimately affects how humans view and treat nature. The author considers this reduction to be one of the fundamental causes of the ongoing global environmental crisis. Therefore, the cosmological view of the Ikhwan al-Shafa', which views nature holistically, has now found its relevance again in efforts to overcome these problems.